(untitled) (Research, Society and Development, 2024)
This study addresses the biodiversity system of the Amazon forest and the origin of socio-biodiversity products. Controlling common belief, the use of conventional agricultural practices is demonstrated to not result in adverse socio-environmental impacts, contributing to the preservation of the ecosystem. Objective: to analyze the bioeconomy in the context of socio-biodiversity in the Amazon with a focus on the state of Pará, Brazil, building interactions between the sustainable extractivism of traditional peoples and family producers, with special emphasis on the climate issue. Method: Bibliographic research with a descriptive and exploratory qualitative approach. Data collection was carried out in consultations on Public Platforms, Scielo and Google Scholar of primary and secondary sources through publications of articles, books, magazines, newspapers, annals, which helped in the construction of the theoretical contribution. Results: 20 publications were selected, which provide discussions by the main authors pointing out tools that support zero deforestation, preserve and reconstitute forests in their socio-biodiversity. Final considerations: The importance of criticism regarding the preservation of the Amazon forest is reinforced, not only for the maintenance of traditional people and their culture, in view of family producers who seek to preserve their territory and extract products in a sustainable way for subsistence.